Distribution and molecular diversity of Paranoplocephala kalelai (Tenora, Haukisalmi & Henttonen, 1985) Tenora, Murai & Vaucher, 1986 in voles (Rodentia: Myodes) in Eurasia - Krivopalov, Anton V.; Vlasenko, Pavel G.; Abramov, Sergey A.; Akimova, Lyudmila; Barkhatova, Alina; Dokuchaev, Nikolai; Gromov, Anton; Konyaev, Sergey; Lopatina, Natalia; Vlasov, Egor; Zakharov, Evgeny S. (Diversity)
Cestodes Paranoplocephala kalelai, which parasitizes in the small intestine of Myodes voles and is distributed in northern Fennoscandia, was found in six habitats in the Asian part of Russia and eastern Kazakhstan, which indicates a wider distribution of P. kalelai on the continent. Analysis of mtDNA showed that P. kalelai is characterized by significant molecular variability in Eurasia. This study complements the data on the distribution of P. kalelai and provides the first molecular data from the territory of Russia and Kazakhstan. The sequence variability of two mitochondrial genes cox1 and nad1 of P. kalelai was studied in two species of voles: gray red-backed Myodes rufocanus and northern red-backed vole Myodes rutilus. Five haplotype groups in the cox1 and nad1 gene networks were identified, and the existence of two mtDNA lines in P. kalelai outside northern Fennoscandia was confirmed. The geographical distribution of the identified haplotypes suggests that the foothills of the Altai-Sayan mountains and southern West Siberia may serve as a refugium for P. kalelai during repeated glaciations.